2022
DOI: 10.3390/life12060779
|View full text |Cite
|
Sign up to set email alerts
|

A Serious Game for the Prevention of Obesity in School Children–Impact of Parent’s Involvement: A Randomized Controlled Trial

Abstract: Serious games convey information and use interactive components to reinforce and train behaviours. A serious game addressing nutrition, physical activity and stress coping—the Kids Obesity Prevention Program (KOP)—was previously evaluated for efficacy in children. This study aimed at evaluating the KOP-game regarding: (i) its acceptance and efficacy with respect to parents of primary school children receiving the same game intervention as the children; and (ii) whether the children could benefit by parental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…Additionally, ED lowering strategies are flexible and diverse and can be adapted to different dietary patterns, food preferences and cultural characteristics [ 2 , 17 , 18 ]. In line, two randomized controlled trials have shown that already primary school children can understand and are able to apply ED knowledge to their daily routine, even at six months follow-up [ 86 , 87 ]. Taken together, these are strong arguments for increase integration of ED manipulation as dietary strategy in prevention and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ED lowering strategies are flexible and diverse and can be adapted to different dietary patterns, food preferences and cultural characteristics [ 2 , 17 , 18 ]. In line, two randomized controlled trials have shown that already primary school children can understand and are able to apply ED knowledge to their daily routine, even at six months follow-up [ 86 , 87 ]. Taken together, these are strong arguments for increase integration of ED manipulation as dietary strategy in prevention and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Kaledo board game developed by Viggiano et al ( 59 ) is a multiple player serious game proven to make players live a healthy lifestyle by instigating healthy eating behavior. Likewise, the Kid Obesity program Game (KOP) and FoodBotFactory are single-player serious games designed by Weiland et al ( 64 ) and Brown et al ( 65 ). Both games demonstrate how serious games maintain high nutritional knowledge in children who play the game.…”
Section: Discussionmentioning
confidence: 99%
“…Für die praktische Umsetzung des Energiedichte-Prinzips gibt es gute Literatur, die auch für den Laien verständlich ist 16 70 71 . Meine Arbeitsgruppe selbst arbeitet an der Umsetzung der Thematik in attraktiven Lernspielen für Kinder und Erwachsene, die jedoch derzeit nur im Rahmen von Forschungsprojekten eingesetzt werden 13 14 . In unserer aktuell laufenden großen STARKIDS-Studie – Stufenmodell Adipositas-Therapie im Kindes- und Jugendalter 72 , einer cluster-randomisierten kontrollierten Studie mit 1000 Studienteilnehmer*innen, wird das Energiedichteprinzip als Ernährungsstrategie erstmals auf seine Wirksamkeit bei Adipositas im Kinder- und Jugendbereich untersucht.…”
Section: Anwendung Des Energiedichte-prinzipsunclassified
“…Gleichzeitig sind die Strategien zur Reduktion der Energiedichte flexibel und vielfältig und können auf verschiedene Ernährungsmuster, Nahrungsmittelvorlieben und kulturelle Besonderheiten angepasst werden 10 11 12 . Zwei randomisierte, kontrollierte Studien konnten zeigen, dass bereits Grundschulkinder das Energiedichte-Prinzip verstehen und anwenden können, selbst noch im 6 Monate follow-up 13 14 . Die Deutsche Gesellschaft für Ernährung hat das Energiedichte-Prinzip als Ernährungsstrategie im Rahmen der Gewichtsregulation anerkannt 15 .…”
Section: Introductionunclassified